Study of Optimal Perimetric Testing in Children (OPTIC): Feasibility, Reliability and Repeatability of Perimetry in Children. - Dipesh E Patel; Phillippa M Cumberland; Bronwen C Walters; Isabelle Russell-Eggitt; Jugnoo S Rahi; OPTIC study group (PLoS ONE)
Purpose To investigate feasibility, reliability and repeatability of perimetry in children. Methods A prospective, observational study recruiting 154 children aged 5-15 years, without an ophthalmic condition that affects the visual field (controls), identified consecutively between May 2012 and November 2013 from hospital eye clinics. Perimetry was undertaken in a single sitting, with standardised protocols, in a randomised order using the Humphrey static (SITA 24-2 FAST), Goldmann and Octopus kinetic perimeters. Data collected included test duration, subjective experience and test quality (incorporating examiner ratings on comprehension of instructions, fatigue, response to visual and auditory stimuli, concentration and co-operation) to assess feasibility and reliability. Testing was repeated within 6 months to assess repeatability. Results Overall feasibility was very high (Goldmann=96.1%, Octopus=89% and Humphrey=100% completed the tests). Examiner rated reliability was 'good' in 125 (81.2%) children for Goldmann, 100 (64.9%) for Octopus and 98 (63.6%) for Humphrey perimetry. Goldmann perimetry was the most reliable method in children under 9 years of age. Reliability improved with increasing age (multinomial logistic regression (Goldmann, Octopus and Humphrey), p<0.001). No significant differences were found for any of the three test strategies when examining initial and follow-up data outputs (Bland-Altman plots, n=43), suggesting good test repeatability, although the sample size may preclude detection of a small learning effect. Conclusions Feasibility and reliability of formal perimetry in children improves with age. By the age of 9 years, all the strategies used here were highly feasible and reliable. Clinical assessment of the visual field is achievable in children as young as 5 years, and should be considered where visual field loss is suspected. Since Goldmann perimetry is the most effective strategy in children aged 5-8 years and this perimeter is no longer available, further research is required on a suitable alternative for this age group.